Pengembangan Sistem Pengelompokan Belajar Mahasiswa pada Matakuliah Struktur Data dengan Metode K-Means - Yogi Yunefri; Eddisyah Putra Pane; Sutejo Sutejo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The development of science and technology requires tertiary institutions as formal education institutions, to be able to produce qualified and competent graduates. Learning about higher education needs to be more innovative and creative in producing learning and responsive to labor needs.